PENGARUH PENGGUNAAN MEDIA KONKRET UNTUK MENUMBUHKAN MINAT PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA DISEKOLAH DASAR - Ihwana (Global Education Trends, 2024)
Problems related to the lack of interest of students in learning mathematics, as a result, have triggered changes in views, and awareness has arisen, especially among policymakers, the aim is to make mathematics learning more meaningful, providing students with relevant competencies, improving the quality and making the learning/teaching process easier for them. students and teaching staff. This research aims to provide references or additions to mathematical disputes. This article is a search via Google Scholar. The method used in this article is the literature review method. Where the essence of the aim of this research is to determine the disparity in problem-solving abilities in mathematics learning which is assisted by concrete media among students. Where the results of this research are very good and positive for the development of the use of concrete media. It can be concluded that the use of concrete media or real media for students' wishes will have a very positive impact, especially as students can express their appreciation for mathematics. For this reason, the use of concrete media is very effective in the learning and teaching process.